2022
DOI: 10.3389/fped.2022.816221
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parental Occupational Balance, Subjective Health, and Clinical Characteristics of VLBW Infants

Abstract: ObjectiveVery low birthweight (VLBW) infants have an increased risk of mortality and frequently suffer from complications, which affects parental occupational balance. Occupational balance is the satisfaction with one's meaningful activities, which include everyday activities that people need to, want to, and are expected to do. In contrast to work-life balance, the construct of occupational balance addresses different activities equally and it applies to all persons, regardless of whether they are working or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…Our results show that additional negative impact on parental stress resulted from visitation restrictions during the pandemic. In detail, we observed a significant increase in self-reported anxiety in mothers of preterm infants before and during the pandemic, consistent with the literature 12 , 22 , 23 , reporting increased maternal stress during the pandemic. Emotionally distressed parents find it more challenging to fulfill their roles in caring for, supporting, and raising their infant 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that additional negative impact on parental stress resulted from visitation restrictions during the pandemic. In detail, we observed a significant increase in self-reported anxiety in mothers of preterm infants before and during the pandemic, consistent with the literature 12 , 22 , 23 , reporting increased maternal stress during the pandemic. Emotionally distressed parents find it more challenging to fulfill their roles in caring for, supporting, and raising their infant 24 .…”
Section: Discussionsupporting
confidence: 92%
“…The historical control group consisted of families of preterm infants who took part in a previous study about the occupational balance in parents of premature infants performed during 2018 and 2019 at the perinatal center of the Medical University Vienna using the same questionnaires (Ethics 1891/2015) 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the impact of OB on health and individuals’ satisfaction with life, any imbalance in occupation can affect health (Backman, 2004; Dür et al, 2022; Parnell, 2022; To-Miles et al, 2022; Wilcock et al, 1997); therefore, instruments measuring OB are useful and fundamental. The OBQ11 assesses a comprehensive concept of OB and it can determine the level of individuals’ OB in a short period of time in comparison to similar assessment tools.…”
Section: Introductionmentioning
confidence: 99%
“…An initial search of MEDLINE identified articles with the relevant terms. Studies explored concepts, such as parental occupational balance in parents of babies born at a very low birth weight who were admitted to a NICU, 22 the experiences of fathers with inpatient premature neonates who experienced occupational disruption, 23 and a cross-sectional study on occupational imbalances in parents following the birth of a baby born preterm and admitted to a NICU. 24 A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted and no current or in-progress scoping reviews or systematic reviews on the topic were identified.…”
Section: Introductionmentioning
confidence: 99%
“…An initial search of MEDLINE identified articles with the relevant terms. Studies explored concepts, such as parental occupational balance in parents of babies born at a very low birth weight who were admitted to a NICU, 22 the experiences of fathers with inpatient premature neonates who experienced occupational disruption, 23 and a cross-sectional study on occupational imbalances in parents following the birth of a baby born preterm and admitted to a NICU 24 …”
Section: Introductionmentioning
confidence: 99%